Pengaruh Insektisida Nabati Daun Galam (Melaleuca cajuputi roxb.) Terhadap Serangan Hama Perusak Daun Pada Tanaman Sawi - Mohammad Taopik; Samharinto Soedijo; Helda Orbani Rosa (www.ulm.ac.id, 2022)
The productivity of mustard (Brassica juncea L.) in Indonesia has increased in 2015-2018, in line with the increasing demand for this vegetable. One of the obstacles in the cultivation of mustard is the attack of leaf destroying pests. An alternative solution to control pests is to use natural ingredients from the galam plant (Melaleuca cajuputi Roxb.). The purpose of this study was to examine the effect of galam leaf insecticide to suppress leaf destroying pests on mustard plants. The study used fresh galam leaf extract as the main ingredient in the manufacture of vegetable insecticides, which were applied in various doses. The research place in a vegetable plantation, Guntung Payung Village, North Loktabat District, Banjarbaru and was carried out for 40 days from seeding to harvesting. This study used an experimental method with a one-factor Completely Randomized Design (CRD) consisting of 5 concentration treatments and 2 controls with 4 replications. The results showed a very significant effect on the intensity of pest attack on the 4th observation. The intensity of the attack of mustard leaf destroying pests from the highest to the lowest was shown by water control (K) treatment of 26.6%, galam leaf extract 10% ( G5) 21.3%, Galam leaf extract 6% (G3) 20.5%, Galam leaf extract 8% (G4) 17.7%, Galam leaf extract 2% (G1) 15.3%, Galam leaf extract 4 % (G2) 14.2% and Chemical control (M) 7.9%.